2011
DOI: 10.1111/j.1365-277x.2011.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

The diet quality of adult women participating in a behavioural weight-loss programme

Abstract: Participation in a 16-week behavioural weight-loss programme significantly improved diet quality and reduced dietary energy density and energy intake in adult women. However, despite the overall increase in diet quality score, there were deficiencies in key micronutrients in the diets of most women at the conclusion of the 16-week study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
6
18
0
1
Order By: Relevance
“…Changes in food choices were consistent with results from other studies in which higher diet quality scores reflected lower consumption of meat [5,65,66], alcohol [33,67] and discretionary food items [29,31]. The observed increased consumption of fruit (found with APDQS and DQT), non-starchy vegetables (found with DQT), tomato and other vegetables (found with APDQS) was also congruent with other studies associating higher intakes of vegetables and fruits associated with high diet quality [65,66].…”
Section: Changes In Food Choicessupporting
confidence: 81%
See 3 more Smart Citations
“…Changes in food choices were consistent with results from other studies in which higher diet quality scores reflected lower consumption of meat [5,65,66], alcohol [33,67] and discretionary food items [29,31]. The observed increased consumption of fruit (found with APDQS and DQT), non-starchy vegetables (found with DQT), tomato and other vegetables (found with APDQS) was also congruent with other studies associating higher intakes of vegetables and fruits associated with high diet quality [65,66].…”
Section: Changes In Food Choicessupporting
confidence: 81%
“…In the trial context, we found decreased intakes of grain foods as have others [5], but not all [33,[66][67][68]. In these latter studies, reporting high intakes of grain based foods from wholegrain sources was representative of higher diet quality.…”
Section: Changes In Food Choicessupporting
confidence: 58%
See 2 more Smart Citations
“…However, in the absence of clinically significant weight loss, the implications of these studies for simultaneously addressing diet quality and weight control are lacking. In a large observational study of the general U.S. adult population, weight gain was strongly associated with consumption of lower quality foods and weight loss was associated with consumption of higher quality foods (25), and in two intervention studies in the general population of obese adults, diet quality as measured at post-intervention only was associated with amount of weight loss (23, 26). To our knowledge, no studies in the literature have examined whether change in diet quality pre to post intervention is associated with change in weight during an intervention.…”
Section: Introductionmentioning
confidence: 99%